QSAR Studies on Hetaryl Imidazoles Derivatives as Novel Dual Inhibitors of Vascular Endothelial Growth Factor Receptors I and II - Tripathi, Tanvee; Mishra, J.P. (Asian Journal of Chemistry, 2010)
The QSAR studies have been carried out on 19-hetaryl imidazoles derivatives, which were reported as inhibitor of vascular endothelial growth factor receptors (VEGFR). The present study was undertaken to determine the physico chemical parameters, which govern the anticancer activity of the given series of drug molecules. The best QSAR model thus obtained, have high statistical significance (> 99.9 %) and moderate correlation coefficient (r = 0.85) led us to know that the activity of these compounds is mainly influenced by substitutions (R) done at meta position of benzene ring and presence of 4-pyridine group at Ar position is found to be important for activity of given series of drug molecules.